2022
DOI: 10.1177/10775463221124976
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flexural and torsional vibration band gaps in phononic crystal beam

Abstract: Phononic crystals (PCs) play an important role in the reduction of vibration within a targeted frequency range. Most research of the one-dimensional PCs focuses on the properties or applications of the flexural band gaps; however, practically, the broadband environmental excitations also induce the torsional vibration. Hence, this paper studies a two-degrees-of-freedom local resonance (2DOF-LR) phononic crystal, which can both suppress the propagation of flexural and torsion waves in the same frequency range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is shown that the PC has both local resonance low-frequency bandgap and acoustic black hole high-frequency bandgap and a better damping effect for high-frequency and low-frequency excitation. Aiming at the problem of low-frequency vibration control, Wang and his collaborators [10] investigated a vibrational band gap of a locally resonant PC thin plate. They confirmed the hindering effect of thin plates on wave propagation within the vibrating bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the PC has both local resonance low-frequency bandgap and acoustic black hole high-frequency bandgap and a better damping effect for high-frequency and low-frequency excitation. Aiming at the problem of low-frequency vibration control, Wang and his collaborators [10] investigated a vibrational band gap of a locally resonant PC thin plate. They confirmed the hindering effect of thin plates on wave propagation within the vibrating bandgap.…”
Section: Introductionmentioning
confidence: 99%